Nurses’ Readiness to Manage Patients Following Suicide Attempts in Hospital Settings: A Systematic Review - Anggit Dwi Retno Murni; Shanti Wardaningsih (Journal of Public Health Sciences, 2026)
Suicide remains a major public health concern worldwide, and nurses play a critical role in managing patients following suicide attempts. Nurses’ readiness is essential to ensure patient safety and prevent recurrent suicidal behaviors. However, evidence suggests that preparedness among nurses varies widely. This systematic review aimed to identify, critically appraise, and synthesize available evidence regarding nurses’ readiness in hospital settings to manage patients following suicide attempts. A systematic review was conducted following PRISMA guidelines. Electronic searches were performed in PubMed, Scopus, and ProQuest databases for articles published between 2021 and 2025. Studies examining nurses’ readiness and related factors in hospital settings were included. Methodological quality was assessed using JBI critical appraisal tools. Data were synthesized narratively. A total of 103 records were identified, and nine studies met the inclusion criteria. Most studies employed quantitative cross-sectional designs, while one study used a quasi-experimental approach. The findings indicated that nurses’ readiness varied considerably and was influenced by multiple factors. Higher readiness was associated with suicide prevention training, clinical experience, positive attitudes, and self-efficacy. Common barriers included high workload, lack of structured training programs, limited organizational support, and absence of clear clinical guidelines. However, the predominance of cross-sectional studies and heterogeneity of outcome measures limited quantitative comparison across studies. Nurses’ readiness to manage patients following suicide attempts remains inconsistent across hospital settings. These findings highlight the importance of implementing regular suicide prevention training programs, establishing clear clinical guidelines, and strengthening organizational support to improve nurses’ readiness in hospital settings and enhance patient safety.